The American Crime: United States Exceptionalism and Global Opinion on Lynching in the Antebellum Era. Issue 2 (1st December 2022) - Webb, Clive
Abstract : Americans have historically claimed that their country is imbued with a moral superiority rooted in its exceptional character. This article shows how overseas critics inverted that idea by arguing that the spread of lynching in the United States during the nineteenth century was evidence of a uniquely lawless and violent society. Their claim was that mob violence had its roots in the individualistic culture of the United States that imbued its citizens with little respect for authority. In holding the United States to account for its failure to meet their own standards of what constituted a civilized country, foreign commentators contributed to an emerging global discourse on human rights.